Encapsulation and characterization of gentamicin sulfate in the collagen added electrospun nanofibers for skin regeneration - Wan Abdul Khodir, Wan Kartini; Abdul Razak, Abdul Hakim; Ng, Min Hwei; Guarino, Vincenzo; Darnis, Deny Susanti (MDPI, 2018)
In the current practice, the clinical use of conventional skin substitutes such as autogenous skin grafts have shown several problems, mainly with respect to limited sources and donor site morbidity. In order to overcome these limitations, the use of smart synthetic biomaterials is tremendously diffusing as skin substitutes. Indeed, engineered skin grafts or analogues frequently play an important role in the treatment of chronic skin wounds, by supporting the regeneration of newly formed tissue, and at the same time preventing infections during the long-term treatment. In this context, natural proteins such as collagen—natively present in the skin tissue—embedded in synthetic polymers (i.e., PCL) allow the development of micro-structured matrices able to mimic the functions and to structure of the surrounding extracellular matrix. Moreover, the encapsulation of drugs, such as gentamicin sulfate, also improves the bioactivity of nanofibers, due to the efficient loading and a controlled drug release towards the site of interest. Herein, we have done a preliminary investigation on the capability of gentamicin sulfate, loaded into collagen-added nanofibers, for the controlled release in local infection treatments. Experimental studies have demonstrated that collagen added fibers can be efficaciously used to administrate gentamicin for 72 h without any toxic in vitro response, thus emerging as a valid candidate for the therapeutic treatment of infected wounds.